LM가이드의 예압에 따른 블록의 변형과 접촉응력에 대한 연구 - 정효진; 안태길; 박현섭; 최시근; 김명현; HyoJin Jung; TaeKil Ahn; HyunSub Park; Si-Geun Choi; Myunghyun Kim (한국트라이볼로지학회지, 2025)
LMGuides are essential mechanical components that are widely used in precision machinery and industrial automation systems as they ensure smooth and accurate linear motion while supporting high static and dynamic loads. Among the key design parameters, the preload plays a critical role in enhancing the system stiffness, reducing vibration, and improving the positioning accuracy. However, an inappropriate or excessive preload can lead to negative effects such as increased internal friction, stress concentration, and a significant reduction in the fatigue life of the components. This study investigates the effect of the preload on block deformation and contact stress distribution within linear guide systems through numerical analysis based on the Hertzian contact theory. Finite element analysis is conducted under various preload levels, specifically corresponding to 2% and 5% of the dynamic load rating, to evaluate the mechanical behavior of the system. The simulation results indicate that increasing the preload effectively reduces block deformation, contributing to improved rigidity and load-bearing capacity. However, beyond an optimal preload range, the contact stress concentrates, which may accelerate wear or cause premature failure of the components. These findings offer valuable insights for designers and engineers to optimize preload settings in high-precision applications where accuracy, reliability, and durability are critical. Future research will focus on dynamic load conditions and fatigue life analysis to develop more comprehensive design guidelines.